2017
DOI: 10.3389/fphys.2016.00669
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Nasal Obstruction during Later Growth Periods Affects Craniofacial Muscles in Rats

Abstract: Nasal obstruction can occur at different life stages. In early stages of life the respiratory system is still under development, maturing during the growth period. Previous studies have shown that nasal obstruction in neonatal rats alters craniofacial function. However, little is known about the effects of nasal obstruction that develops during later growth periods. The aim of this study was to investigate the effects of nasal obstruction during later periods of growth on the functional characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In the present study, we performed unilateral nasal obstruction with reference to the method of Uchima et al Figure shows that there were no significant differences in the body weight among all groups, findings that were similar to those of Uchima et al Although the age of the rats and methods in our study differed, mild respiratory disorders over long periods of time do not seem to affect body weight, findings that are consistent with those of Funaki et al Therefore, we believe that this method is suitable for investigating the effects of unilateral nasal obstruction on changes in the craniofacial morphology.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we performed unilateral nasal obstruction with reference to the method of Uchima et al Figure shows that there were no significant differences in the body weight among all groups, findings that were similar to those of Uchima et al Although the age of the rats and methods in our study differed, mild respiratory disorders over long periods of time do not seem to affect body weight, findings that are consistent with those of Funaki et al Therefore, we believe that this method is suitable for investigating the effects of unilateral nasal obstruction on changes in the craniofacial morphology.…”
Section: Discussionsupporting
confidence: 88%
“…Humans breathe through their mouth when the nostrils on both sides are blocked, while rats cannot breathe through their mouth . Therefore, we blocked the nose unilaterally in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated that oral breathing induces chewing activity (24), but whether the decrease in chewing activity will reduce the bone density of alveolar bones remains unclear. Oral breathing is known to affect craniofacial muscle activity (6,8,9,10). Nonetheless, further studies are needed to explore the relationship between craniofacial muscle activity and the density of alveolar bones.…”
Section: Discussionmentioning
confidence: 99%
“…Oral breathing has an important impact on the growth and development of craniofacial structures (1,2,3,4,5). Animal experiments demonstrated that changes in breathing patterns from the nasal cavity to the oral cavity can induce changes in craniofacial muscle activity (6,7,8,9,10,11). Recent studies have focused on the effect of oral breathing on the morphology of maxillofacial (12,13).…”
mentioning
confidence: 99%
“…Our previous studies showed an increase in the tongue-protruding forces after unilateral nasal obstruction in growing rats, by changing the muscle contractile properties, while oxygen saturation levels were also lower after nasal obstruction 13 , 14 . It has been suggested that the muscle force and contractile properties are affected by the cross-sectional area of muscle fiber 15 .…”
Section: Introductionmentioning
confidence: 90%